Answer:
2x + 7
Explanation:
Simplify
6x2 + 11x - 35 / 3x - 5
2.1 Factoring 6x2 + 11x - 35
The first term is, 6x2 its coefficient is 6 .
The middle term is, +11x its coefficient is 11 .
The last term, "the constant", is -35
Step-1 : Multiply the coefficient of the first term by the constant 6 • -35 = -210
Step-2 : Find two factors of -210 whose sum equals the coefficient of the middle term, which is 11 .
-210 + 1 = -209
-105 + 2 = -103
-70 + 3 = -67
-42 + 5 = -37
-35 + 6 = -29
-30 + 7 = -23
-21 + 10 = -11
-15 + 14 = -1
-14 + 15 = 1
-10 + 21 = 11 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -10 and 21
6x2 - 10x + 21x - 35
Step-4 : Add up the first 2 terms, pulling out like factors :
2x • (3x-5)
Add up the last 2 terms, pulling out common factors :
7 • (3x-5)
Step-5 : Add up the four terms of step 4 :
(2x+7) • (3x-5)
Which is the desired factorization
2.2 Cancel out (3x-5) which appears on both sides of the fraction line.
Final result : 2x + 7